2019
DOI: 10.5937/bezbednost1901025m
|View full text |Cite
|
Sign up to set email alerts
|

Simple visual reaction time in students of Academy of Criminalistic and Police Studies

Abstract: The aim of this paper is to determine gender based differences as well as the initial standard values for evaluation of simple visual reaction time in both male and female students of the Academy of Criminalistic and Police Studies (ACPS)in Belgrade. The method used in this research was laboratory testing. All datasampling was performed using the specially designed testing software that recorded reaction time with 1 ms precision. The variable used in this research, that is Simple Visual Reaction Time (SVRT), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Although previous findings have shown that females have slower reaction time compared to males (Bleecker, Bola-Wilson, Agnew, & Meyers, 1987;Dane & Erzurumluoglu, 2003;Der & Deary, 2006) a trend of equation of reaction time between females and males has been reported by Silverman (2006). The results of our study have shown that tested female cadet handball players have an overall SVRT mean of 190.07±2.92 ms which is a slightly shorter RT compared to female ACPS (Academy of Criminalistic and Police Studies) students tested with the same methodology who had a mean SVRT of 202.30±18.89 ms (Marković, Vučković, & Janković, 2019). The presented results of the overall sample as well as the results of the respective subsamples of cadet and junior players that have a SVRT mean value of 194.28±3.80 and 184.73±4.31 ms can be directly compared with the results of moderately and highly active females who have mean SVRT values of 203.07±19.47 and 191.68±16.57 ms, respectively (Marković & Dopsaj, 2018).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although previous findings have shown that females have slower reaction time compared to males (Bleecker, Bola-Wilson, Agnew, & Meyers, 1987;Dane & Erzurumluoglu, 2003;Der & Deary, 2006) a trend of equation of reaction time between females and males has been reported by Silverman (2006). The results of our study have shown that tested female cadet handball players have an overall SVRT mean of 190.07±2.92 ms which is a slightly shorter RT compared to female ACPS (Academy of Criminalistic and Police Studies) students tested with the same methodology who had a mean SVRT of 202.30±18.89 ms (Marković, Vučković, & Janković, 2019). The presented results of the overall sample as well as the results of the respective subsamples of cadet and junior players that have a SVRT mean value of 194.28±3.80 and 184.73±4.31 ms can be directly compared with the results of moderately and highly active females who have mean SVRT values of 203.07±19.47 and 191.68±16.57 ms, respectively (Marković & Dopsaj, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…In the lack of similar data the presented results can be compared with the results calculated from the data obtained with the same methodology that was used in previous publications. When compared with female ACPS students, an RTV of 9.78±4.78 % and active females that have an RTV at the level of 10.46±7.23 % (Marković & Dopsaj, 2018;Marković et al, 2019) the RTV values found in the samples considered in this research indicate higher levels of acute concentration in trained participants. An explanation for shorter reaction time in physically active participants was proposed by Spirduso (1975) who points out to the possible positive relationship between augmented excitation and continuous demands for fast decision making during sports activities and enhanced neural efficiency, which can possibly also contribute to higher levels of acute concentration, i.e.…”
Section: Discussionmentioning
confidence: 69%
“…If the normal distribution was not given, nonparametric tests were employed. Reaction times were resolved by excluding misses and values below 150 ms as well as all reaction times above 414 ms (75. quartile plus 3*IQR) as outliers ( Baayen and Milin, 2010 ; Marković et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%